A comparative analysis of the BRICS in the International Development Cooperation field - Rinaldi, Augusto Leal (2020)
In the last decade, some changes have occurred in the IDC landscape as developing countries started to assume a prominent role in a topic historically dominated by traditional donors. Among these new players, the BRICS deserve special attention. Using a descriptive and comparative methodology, we analyze the convergences and divergences among these countries regarding their IDC practices. In particular, we tried to answer the following question: How do the BRICS have performed on the IDC field in the last decade? Therefore, we analyzed this variable through four analytical dimensions i) the historical context, ii) the geopolitical context, iii) the institutional context, and iv) the domestic policy context. The general findings suggest that although their IDC policies present some commonalities, they manifest important differences, especially regarding the amount and scope of recipients, and adherence to DAC/OECD guidelines and terminologies.